Well-being in the Advent of Capitalism: Maximization of Utility against Categorical Imperative - Dano, Givheart (Department of Political Sciences, Faculty of Social and Political Sciences, UIN Sunan Ampel Surabaya, 2022)
In the modern capitalist society, the balance between promoting the well-being of the majority and respecting individual rights raises significant moral dilemmas. This paper explores two frameworks of morality: the maximization of utility and the categorical imperative. While the maximization of utility focuses on maximizing overall happiness and well-being, it may require sacrificing the well-being of a few individuals for the greater good. On the other hand, the categorical imperative emphasizes universal moral principles and the inherent dignity of individuals, prioritizing individual rights and justice. In the context of a capitalist society, the paper argues that the categorical imperative holds a more promising approach to well-being. It emphasizes the importance of respecting and protecting the inherent rights and dignity of individuals, ensuring fairness and equality. While capitalism can provide opportunities for economic growth and individual freedoms, it requires ethical considerations and regulations to ensure that it operates within a framework that upholds human rights. The tension between these frameworks challenges our perspectives on morality and highlights the complex ethical dilemmas that arise in a capitalist society. Ultimately, finding a balance between promoting well-being and respecting individual rights is crucial for creating a just and inclusive society within the capitalist framework.